Penyelesaian Sengketa Investasi di Dalam The Regional Comprehensive Economic Partnership (RCEP) Agreement: Peniadaan Mekanisme Investor-State Dispute Settlement (ISDS) - Harisah, Himatul (Officium Notarium, 2025)
This research aims to analyze the effectiveness of the ISDS exclusion provision in the dispute settlement mechanism stipulated in RCEP for Indonesia. This type of research uses a normative legal approach based on relevant international treaties, doctrines, and jurisprudence and a comparative legal approach, where researchers will compare investment dispute resolution applied by several countries. The research concludes that the exclusion of the ISDS mechanism in RCEP is the right move taken by the Government of Indonesia so that the country has the policy space to establish national policies that protect national interests. In the event that later on, based on the results of the review of the exclusion of ISDS mechanism, RCEP member countries agree to implement dispute settlement through the ISDS mechanism, then Indonesia needs to propose to be able to include the obligation to settle disputes through the domestic court mechanism for the first occasion and there is a need to strengthen the existing legal instruments, namely Presidential Decree No. 31/2012, either through amendments or the making of higher and more comprehensive laws and regulations.